2x2 - 20x - 106 = 0
(20 +/- sqrt(400 + 848))/4
=(20 +/- sqrt 1248)/4
= (20 +/- 35.33)/4
= 55.33/4 or -15.33/4
= 13.83 or -3.83
Chat with our AI personalities
x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0
x2 + 20x + 4 = 0 x2 + 20x + 100 = 96 (x + 10)2 = 96 x + 10 = ±961/2 x = -10 ±961/2 x = -10 ±4√6
4 equals 2x2, 6 equals 2x3
Set all numbers and variables equal to zero. (2x3)-(3x2)-(20x)-21=0 Next, follow the order of p.e.m.d.a.s. 6-6-20x-21=0 -20x-21=0 Separate the numbers and variables -20x=21 x= -21/20
Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3